Novel bayberry-and-honeycomb-like magnetic surface molecularly imprinted polymers for the selective enrichment of rutin from Sophora japonica. (15th September 2021) - Song, Huijia; Zhang, Haipin; He, Yulian; Gao, Ruixia; Wang, Yue; Wang, Wenting; Pfefferle, Lisa D.; Tang, Xiaoshuang; Tang, Yuhai
Highlights: Novel bayberry-and-honeycomb-like magnetic imprinted polymers were designed. Hyperbranched phenylboric acid was fabricated and covalently modified on the carrier. Abundant recognition sites with high-affinity and regular-distribution were formed. The imprinted nanomaterials show high adsorption capacity and good selectivity. Rutin was successfully extracted from Sophora japonica by the developed method. Abstract: Rutin (RT), a widely distributed natural flavonoid compound, has been generally utilized as an important active ingredient owing to its considerable biomedical and economic value. Inspired by the structure features of densely-packed bayberry and well-orientated honeycomb, a novel type of magnetic molecularly imprinted polymers (HB-TI-MMIPs) with abundant high-affinity and uniformly-distributed binding sites was rationally constructed for the selective enrichment of RT from Sophora japonica. The polymerization conditions, physicochemical properties, and adsorption performance of the imprinted nanomaterials were systematically investigated. The optimized HB-TI-MMIPs display a high adsorption capacity, fast adsorption rate, and satisfactory selectivity towards RT. Meanwhile, the proposed analytical methodology using HPLC, with HB-TI-MMIPs as adsorbents, successfully applied to enrich and detect RT from Sophora japonica with high recoveries (87.2–94.6%) and good RSDs (lower than 4.3%). Therefore, the fabricated HB-TI-MMIPs with a fast magnetic responsivity and desirable adsorption performance would be attractive in plant active ingredients extraction fields.